2017
DOI: 10.1111/jace.14952
|View full text |Cite
|
Sign up to set email alerts
|

Ferroelectric and magnetic properties in (1−x)BiFeO3x(0.5CaTiO3–0.5SmFeO3) ceramics

Abstract: Multiferroic ceramics were prepared and characterized in (1−x)BiFeO3–x(0.5CaTiO3–0.5SmFeO3) system by a standard solid‐state reaction process. The structure evolution was investigated by X‐ray diffraction and Raman spectrum analyses. The refinement results confirmed the different phase assemblages with varying amounts of polar rhombohedral R3c and nonpolar orthorhombic Pbnm as a function of the substitution content. In the compositions range of 0.2≤x≤0.5, polar R3c and nonpolar Pbnm coexisted, which was referr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 46 publications
1
26
0
Order By: Relevance
“…We reveal this unusual phase transition in a lead-free relaxor composition of [(Bi 1/2 Na 1/2 ) 0.95 Ba 0.05 ] 0.98 La 0.02 TiO 3 (BNT2La) in which a ferroelectric phase can be readily formed during electric poling [30,31]. The induced ferroelectric phase remains metastable upon field removal.…”
Section: ]mentioning
confidence: 78%
See 1 more Smart Citation
“…We reveal this unusual phase transition in a lead-free relaxor composition of [(Bi 1/2 Na 1/2 ) 0.95 Ba 0.05 ] 0.98 La 0.02 TiO 3 (BNT2La) in which a ferroelectric phase can be readily formed during electric poling [30,31]. The induced ferroelectric phase remains metastable upon field removal.…”
Section: ]mentioning
confidence: 78%
“…1. The virgin state ceramic is a non-ergodic relaxor at room temperature [30], as indicated by the strong frequency dispersion in the dielectric behavior ( Fig. 1a) and representative nanometer-sized domains in its microstructures (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Download to IP: 129.186.176.188 On: Mon, 12 Dec tilting. 8,11,18,19 Therefore, the rhombohedral R3c and tetragonal P4bm phases coexist in the BNT-100xTa (1.0 x 3.0) ceramics in the form of nanometer-sized polar domains. It is interesting to observe that the 1 = 2 {ooe}-type superlattice spots are much stronger than the 1 = 2 {ooo}-type spots in the [112] diffraction patterns, indicating that the tetragonal phase is dominant in these compositions.…”
Section: -mentioning
confidence: 98%
“…6 Among the lead-free solid solution systems reported in the literature, (Bi 1/2 Na 1/2 )TiO 3 -based compositions 7,8 seem to be most likely to develop ultrahigh strains under applied electric fields. [9][10][11] For example, a 2007 study by Zhang et al reported a very large electrostrain of 0.45% in the polycrystalline ceramic 0.92(Bi 1/2 Na 1/2 )TiO 3 -0.06BaTiO 3 -0.02 (K 0.5 Nb 0.5 )NbO 3 under an applied field of 80 kV/cm. 9 Since then, even higher strains (0.48%) have been reported, [12][13][14][15] primarily in modified [Bi 1/2 (Na 1-x K x ) 1/2 ]TiO 3 compositions.…”
mentioning
confidence: 99%
“…49,50,51 The ternary system BNT-BKT-BT, for example, has been thoroughly investigated due to the excellent piezoelectric properties with a d 33 Sintering was conducted at 1150 o C for 3 hours.…”
mentioning
confidence: 99%